ByzRev 05.2023.015: Spyridon Tzounakas – Stella Alekou – Stephen J. Harrison (eds), The Reception of Ancient Cyprus in Western Culture : (Trends in Classics, Supplementary Volumes 139). Berlin: De Gruyter 2023. - Kim, Young Richard (The Byzantine Review, 2023)
Spyridon Tzounakas – Stella Alekou – Stephen J. Harrison (eds), The Reception of Ancient Cyprus in Western Culture (Trends in Classics, Supplementary Volumes 139). Berlin: De Gruyter 2023. VIII, 314 S. – ISBN 978-3-11-099665-4 (126.99, € 109.95)